Convenience Voting and Technology - Smith, Claire M. author. aut Link
XVI, 219 p.
Keywords: One of modern democracy's biggest challenges is the overseas voter.This book is the first of its kind to explore the issues of military and overseas voting, an often neglected voting bloc, by investigating the successfulness of overseas voting initiatives, technologies, and policy efforts.